Inhibitory Effects of Polyphenols-Rich Components From Three Edible Seaweeds on Inflammation and Colon Cancer in vitro - Yi, Lingxiao; Wang, Qi; Luo, Haiyan; Lei, Daqing; Tang, Zhonghai; Lei, Sijia; Xiao, Hang (Frontiers in Nutrition, 2022)
Polyphenols from edible seaweeds display various health benefits which have not been adequately studied. The current study aimed to characterize the composition of extractable polyphenol-rich components (EPCs) and non-extractable polyphenol-rich components (NEPCs) from three edible seaweeds (Laminaria japonica, Ulva lactuca and Porphyra tenera) and evaluate their anti-inflammatory and anti-colon cancer properties. Both EPCs and NEPCs from three edible seaweeds against lipopolysaccharides (LPS) stimulated nitric oxide in macrophages. Further mechanistic tests revealed that EPCs and NEPCs regulated the expression levels of proinflammatory enzymes, proinflammatory cytokines and antioxidant enzymes in macrophages. Furthermore, EPCs and NEPCs lowered the viability of colon cancer cells, while normal colon cells were not affected. Additionally, EPCs and NEPCs induced cellular apoptosis and led to G0/G1 cell cycle arrest in HCT116 cells. Overall, these results provide a rationale for future animal and human studies designed to examine the anti-inflammatory and chemopreventive capacities of polyphenols-rich components from L. japonica, U. lactuca and P. tenera.